Pengaruh Pelayanan Prima dan Customer Relationship Management terhadap Loyalitas Pasien yang dimediasi oleh Kepuasan dan Kepercayaan - I Gede Suasnawa; A.A.N. Eddy Supriyadinata Gorda (Jurnal Manajemen dan Bisnis, 2017)
ABSTRACTThe study aims to examine Influence in Service Excellence, Customer Relationship Management (CRM) mediated by Patient Satisfaction, Trust to Loyalty in Bali Royal Hospital. This research is an explanatory, using a causal approach. The location of this research is in Bali Royal Hospital. The sampling technique is an incidental sampling with patient criteria who visit Bali Royal Hospital more than twice in the age of 17-65 years and are able to interact, so that the number of samples used in this study amounted to 135 respondents. The data analysis that was used in this study was the CB-SEM (Covariance-Based Structural Equation Modeling). The results of this study are excellent service have positive effect on patient satisfaction and confidence in Bali Royal Hospital. Variable Customer Relationship Management (CRM) has positive effect on patient satisfaction and confidence in General Hospital Bali Royal. Additionally, satisfaction and confidence effect positively on patients' trust in Bali Royal Hospital. The advice that is given to the Hospital Management is further optimize the role of management in terms of operational oversight hospital. Suggested to the other researchers to further examine the factors that influence patient’s loyalty with different variables and indicators which are not contained in this research.